Comparison of structural characteristics and immunoregulatory activities of polysaccharides from four natural plants. Issue 1 (1st January 2020) - Mahabati, Mahepali; Aipire, Adila; Yuan, Pengfei; Liu, Xiaoying; Cai, Shanshan; Aimaier, Alimu; Ziyayiding, Dilinigeer; Yasheng, Mayila; Abudujilile, Dilinazi; Li, Jinyao
ABSTRACT: Polysaccharides have various bioactivities including anti-tumour, antioxidant and immunoregulation, which are correlated with their structural characteristics. Here, four polysaccharides from Glycyrrhiza uralensis (GUPS), Pleurotus ferulae (PFPS), Triticum aestivum (TAPS) and Oryza sativa (OSPS) were purified to compare their structural characteristics and immunoregulatory activities. The data showed that TAPS, OSPS, GUPS and PFPS contained different monosaccharide components and had distinctly structural characteristics. All the four polysaccharides promoted the maturation of dendritic cells (DCs) through TLR4 with different activities. GUPS and PFPS also reduced the phagocytosis of DCs but not for TAPS and OSPS. Importantly, GUPS and PFPS enhanced the Th1 skewing immune response in mice without inflammation. TAPS and OSPS only showed weak immunostimulatory activity in vivo . The immunostimulatory activities of the four polysaccharides were ranked as PFPS = GUPS > TAPS > OSPS.